Efficient Detection of Hydrogen Bonds in Dynamic Regions of RNA by Sensitivity‐Optimized NMR Pulse Sequences1. Issue 40 (14th August 2013) - Dallmann, Andre; Simon, Bernd; Duszczyk, Malgorzata M.; Kooshapur, Hamed; Pardi, Arthur; Bermel, Wolfgang; Sattler, Michael
<x xml:space="preserve">Abstract</x> Improved Sensitivity: Efficient NMR experiments are presented for determining the secondary structure in large and dynamic RNAs using J‐couplings across hydrogen bonds (see picture). The experiments provide up to eight‐fold improved sensitivity and thus enable detection of base pairs in dynamic regions even in large RNAs.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>